The Influence of Environmental Awareness, Environmental Attitudes, and Perceptions of Green Marketing on Consumer Trust in Environmentally Friendly Products in Modern Retail - Sukoco, Andreas Ari; Stefia, Cheryl Marlitta; Haryanto, Budhi; Rohwiyati, Rohwiyati; Fenitra, Rakotoarisoa Maminirina (Journal of Management and Entrepreneurship Research, 2025)
Objective: This study aims to analyze the effects of environmental awareness, environmental attitude, and perceptions of green marketing on consumer trust in eco-friendly products in modern retail. Research Design & Methods: The research employs a quantitative survey design with a purposive random sampling technique, yielding 100 respondents. Data were collected using a questionnaire and analyzed using multiple linear regression in SPSS. Findings: The results show that environmental awareness, environmental attitude, and perceptions of green marketing have positive and significant effects on consumer trust. Implications & Recommendations: Practically, modern retailers need to strengthen the credibility of their green communications (credible certifications/labels, traceability evidence) and enhance consumer education so that sustainability claims are understood and trusted. Contribution & Value Added: The novelty of this study lies in integrating VBN and Signaling Theory within a single model to explain the formation of green trust in Indonesia’s modern retail context. The findings further reinforce the proposition that building green trust requires a combination of consumers’ awareness and positive attitudes together with credible and consistent green marketing signals. The synergy of these factors is crucial for encouraging the adoption of eco-friendly products in modern retail.